Research on innovation of ideological and political education in universities under the background of "Double First-Class" - Ma, Qinjuan; Wang, Pingshui (IJRDO- Journal of Educational Research, 2021)
With the "Double First-Class" put forward, the social demand for education in colleges and universities is more and more high. In college education, ideological and political education occupies a very important position. Based on the background of "Double First-Class", colleges and universities should fully strengthen the reform and innovation of Ideological and political education in order to provide effective guarantee for the development of higher education. This paper mainly introduces the concepts of "Double First-Class" and ideological and political education, analyzes the current situation of ideological and political education in colleges and universities, and deeply discusses the effective innovative measures of ideological and political education in colleges and universities under the background of "Double First-Class", so as to further improve the development of higher education.